Transformasi Digital Administrasi Imigrasi : Studi Implementasi Autogate di Pos Lintas Batas - Daffa Raihan Arya Mas’adi (BADAN PENERBIT STIEPARI PRESS, 2025)
Digital transformation in public administration is an important element in increasing the efficiency and effectiveness of services, including in the immigration sector. This research aims to analyze the implementation of the Autogate system as a form of digitalization of immigration services at National Border Posts (PLBN), especially at PLBN Entikong and Skouw. Autogate is a biometric-based automatic inspection system designed to speed up the immigration process while strengthening security aspects. Using a descriptive qualitative approach, data was collected through document study, in-depth interviews and participant observation. The research results show that Autogate is able to improve service efficiency and supervision, but still faces various challenges such as limited technological infrastructure, human resource readiness, and data security issues. This research emphasizes the importance of adaptive and inclusive implementation strategies, as well as strong national regulatory and policy support to realize sustainable immigration digital transformation.